Comparative proteomic analysis of cold seep clam Archivesica marissinica and shallow water shellfish Ruditapes philippinarum provides insights into the adaptation mechanisms of deep-sea mollusks - Kong, Xue; Wang, Wei; Chen, Sunan; Mao, Ning; Cai, Yuefeng; Li, Yanan; Xia, Sunan; Zhang, Haibin; Shen, Xin (Frontiers in Marine Science, 2024)
Introduction The deep-sea environment is always characterized by high hydrostatic pressure, fluctuating temperatures, heavy metals, darkness, and others. The Vesicomyidae inhabit cold seep zones, hydrothermal vents, and other chemically reduced environments. Methods To enhance the understanding of the adaptation mechanisms of clams in extreme environments, a comprehensive proteomic study was conducted on the cold seep clam Archivesica marissinica and shallow water clam Ruditapes philippinarum. Results A total of 4,557 proteins were identified from the comparative groups. The Gene Ontology results indicated that the differentially expressed proteins (DEP) for the comparative group Rpgill vs. Amgill were enriched in the nitrogen compound metabolic process, and others. The comparative analysis for Amfoot vs. Amgill and Ammantle vs. Amgill revealed significant enrichment of the differential proteins that were involved in metal ion transport, divalent inorganic cation transport, and so on. The Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analysis for the comparative group Rpgill vs. Amgill was significantly enriched in the regulation of actin cytoskeleton, lysosome, and others. The proteins that exhibited differential expression in the cold seep clam’ different tissues were also enriched in important pathways, such as lysosome, fatty acid degradation, nitrogen metabolism. Discussion The further analysis identified crucial response proteins involved in various biological pathways. For example, the pattern recognition receptors, such as galectin and peptidoglycan recognition protein, participated in recognition of symbiotic microorganisms. The lysosome pathway members, such as cathepsin and saposins, were engaged in the degradation process of symbiont proteins during symbiont digestion. Profilin and gelsolin from actin cytoskeleton pathway might be pressure-related proteins. Furthermore, carbonic anhydrases from nitrogen metabolism KEGG pathway provide inorganic carbon for symbiotic bacteria. Additionally, Mn superoxide dismutase plays a role in the scavenging of superoxide anion radicals and antioxidant activity. Then, arginine kinases facilitate the low temperature adaptation of deep-sea shellfish with its cold adaptation characters. These findings offer novel perspectives on the proteins that are implicated in A. marisica’s response to cold seep environments, thereby contributing to the understanding of deep-sea biological adaptation and the preservation of deep-sea ecosystems.